Electrical Properties Assessed by Bioelectrical Impedance Spectroscopy as Biomarkers of Age-related Loss of Skeletal Muscle Quantity and Quality. (15th November 2016) - Yamada, Yosuke; Buehring, Bjoern; Krueger, Diane; Anderson, Rozalyn M; Schoeller, Dale A; Binkley, Neil
Abstract: Skeletal muscle, in addition to being comprised of a heterogeneous muscle fiber population, also includes extracellular components that do not contribute to positive tensional force production. Here we test segmental bioelectrical impedance spectroscopy (S-BIS) to assess muscle intracellular mass and composition. S-BIS can evaluate electrical properties that may be related to muscle force production. Muscle fiber membranes separate the intracellular components from the extracellular environment and consist of lipid bilayers which act as an electrical capacitor. We found that S-BIS measures accounted for 85% of the age-related decrease in appendicular muscle power compared with only 49% for dual-energy x-ray absorptiometry (DXA) measures. Indices of extracellular (noncontractile) and cellular (contractile) compartments in skeletal muscle tissues were determined using the Cole–Cole plot from S-BIS measures. Characteristic frequency, membrane capacitance, and phase angle determined by Cole–Cole analysis together presented a S-BIS complex model that explained 79% of interindividual variance of leg muscle power. This finding underscores the value of S-BIS to measure muscle composition rather than lean mass as measured by DXA and suggests that S-BIS should be highly informative in skeletal muscle physiology.